Differential changes in cyclic adenosine 3′‐5′ monophosphate ( cAMP ) effectors and major Ca 2+ handling proteins during diabetic cardiomyopathy - Chaoul, Victoria; Hanna, Rita; Hachem, Pia; El Hayek, Magali Samia; Nour‐Eldine, Wared; Abou‐Khalil, Pamela; Abi‐Ramia, Elias; Vandecasteele, Grégoire; Abi‐Gerges, Aniella (Journal of cellular and molecular medicine, 2023)
Diabetic cardiomyopathy (DCM) is associated with differential and time‐specific regulation of β‐adrenergic receptors and cardiac cyclic nucleotide phosphodiesterases with consequences for total cyclic adenosine 3′‐5′ monophosphate (cAMP) levels. We aimed to investigate whether these changes are associated with downstream impairments in cAMP and Ca 2+ signalling in a type 1 diabetes (T1D)‐induced DCM model. T1D was induced in adult male rats by streptozotocin (65 mg/kg) injection. DCM was assessed by cardiac structural and molecular remodelling. We delineated sequential changes affecting the exchange protein (Epac1/2), cAMP‐dependent protein kinase A (PKA) and Ca 2+ /Calmodulin‐dependent kinase II (CaMKII) at 4, 8 and 12 weeks following diabetes, by real‐time quantitative PCR and western blot. Expression of Ca 2+ ATPase pump (SERCA2a), phospholamban (PLB) and Troponin I (TnI) was also examined. Early upregulation of Epac1 transcripts was noted in diabetic hearts at Week 4, followed by increases in Epac2 mRNA, but not protein levels, at Week 12. Expression of PKA subunits (RI, RIIα and Cα) remained unchanged regardless of the disease stage, whereas CaMKII increased at Week 12 in DCM. Moreover, PLB transcripts were upregulated in diabetic hearts, whereas SERCA2a and TnI gene expression was unchanged irrespective of the disease evolution. PLB phosphorylation at threonine‐17 was increased in DCM, whereas phosphorylation of both PLB at serine‐16 and TnI at serine‐23/24 was unchanged. We show for the first time differential and time‐specific regulations in cardiac cAMP effectors and Ca 2+ handling proteins, data that may prove useful in proposing new therapeutic approaches in T1D‐induced DCM.